PENGARUH FINANCIAL DISTRESS, OPINI TAHUN SEBELUMNYA, DAN DISCLOSURE TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Ridha Nur Azizah Miriyanto (2022)
This research is a quantitative study with the aim of knowing the effect of financial distress, prior opinion, and disclosure on the acceptance of going concern audit opinion. The population in this study are infrastructure, transportation, and logistics companies listed on the Indonesia Stock Exchange in 2018-2020. The data samples was determined using purposive sampling method and obtained a 178 samples from 58 companies. Hypothesis testing using logistic regression analysis with SPSS version 26 program. Results of this study indicate that financial distress has a significant negative effect on the acceptance of going concern audit opinion, meanwhile prior opinion and disclosure has no significant effect on the acceptance of going concern audit opinion.